Modelling of ballasted railway track foundations under train moving loads - Abu Sayeed, M.; Shahin, Mohamed (New Zealand Geotechnical Society, 2015)
Recent congestion of highways in many countries around the world has led railways to become the most popular means of public transportation, which increased the demand for heavier and faster trains. This requires an investigation into the impact of various design parameters affecting the overall railway track performance. Such an investigation is very important for railway geotechnical engineers to arrive at an optimum plan for track design and maintenance. In this paper, a sophisticated three-dimensional (3D) finite element (FE) modelling is developed to investigate the dynamic response of ballasted railway track subjected to train moving loads. All components of the ballasted railway track system are represented including the rail, sleepers, ballast, sub-ballast and subgrade. The viscous quiet boundaries are used to represent infinite boundary conditions so as to absorb the train induced vibration waves at the boundaries. The FE modelling is validated using field measurement data. A detailed parametric study is carried out to investigate the effects of train speed, and modulus and thickness of ballast, sub-ballast and subgrade on track performance. The track response in terms of rail displacement, ballast, subballast and subgrade surface vertical stresses, surface subgrade strain and track stiffness are presented and their practical implications in relation to track design are discussed.